(untitled) (BIRDEM Medical Journal, 2013)
Objective: To present results from the Bangladesh cohort of the A1chieve study receiving insulin detemir (Levemir) ± oral anti diabetic drugs. Methods: Out of 1093 patients recruited from 49 sites in Bangladesh, 370 were initiated on insulin detemir (Levemir).Study visits were defined as baseline, interim (around 12 weeks from baseline) and final (around 24 weeks from baseline) visit. Results: Glycaemic control was poor in all the groups at baseline. In the entire cohort at 24 weeks, significant reductions from baseline were observed in mean HbA1c (from 10.0 % to 7.2%, p<0.001), FPG (from 10.5 to 6.7 mmol/L, p<0.001) and PPPG (from 15.3 to 8.9 mmol/L, p<0.001) levels. Overall 45.5% of the participants achieved target HbA1c level of < 7% after 24 weeks. The rate of all hypoglycaemic events in the entire cohort reduced from 1.34 (baseline) to 0.12 events/person year after 24 weeks of insulin detemir therapy (p<0.0001). There was no clinically relevant change in body weight in insulin naïve or prior insulin users groups after 24 weeks of insulin detemir therapy. Conclusions: The current study suggests that insulin detemir may be considered as a safe and effective option for initiating insulin therapy for type 2 diabetes in Bangladesh. Birdem Med J 2013; 3(1): 11-18 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17121